Medio Ambiente y Desarrollo en España en los prolegómenos del siglo XXI : Las políticas medioambientales de la U.E. - Sotelo Navalpotro, José Antonio (Observatorio Medioambiental, 2000)
While environmental problems increase, measures to solve present problems or prevent future ones are not taken seriously. Owing to circunstances, the solutions contained in traditional environmental policies are still use full. However, we should aim towards a preventive environmental policy which will enable our country to be a forerunner in what, in the near future from the «Fift» a «Sixth» «Programme» of the European Union.
Keywords: Environmental Policies of the European Union; «Fifth Programme»